X-linked Charcot–Marie–Tooth Disease Presenting with Stuttering Stroke-like Symptoms - Hardy, Duriel I.; Licht, Daniel J.; Vossough, Arastoo; Kirschen, Matthew P. (Neuropediatrics, 2019)
X-linked Charcot–Marie–Tooth disease (CMTX1) is the second most common form of Charcot–Marie–Tooth disease (CMT). It is caused by a mutation in the gap junction β 1 (GJB1) gene, which encodes for connexin-32. In addition to the peripheral neuropathy and foot deformities observed in classic CMT, central nervous system symptoms and magnetic resonance imaging (MRI) signal abnormalities in the brain have been reported in patients with CMTX1. Here we describe two cases of adolescent males who presented with stuttering neurologic deficits that were initially suggestive of acute ischemic stroke and were ultimately diagnosed with genetically confirmed CMTX1. Both patients had evidence of T2 hyperintensity and decreased diffusion on MRI in the centrum semiovale, posterior corona radiata, posterior periventricular white matter, and corpus callosum. Though rare, these cases illustrate the importance of comprehensive neurologic history, physical examination, and appropriate diagnostic evaluation.
Keywords: X-linked Charcot–Marie–Tooth disease; gap junction β 1 gene; neuropathy; stroke-like symptoms